Milk Production and Evaluation in Farms Raised Anatolian Water Buffalo (Bubalus bubalis); A Case Study of Igdir Province - Yilmaz, I; Yurt, B; Şahin, O (Journal of the Hellenic Veterinary Medical Society, 2024)
This study was conducted by carrying out a questionnaire with 98 enterprise owners rearing Anatolian water buffalo in 2015 in Igdir city of Turkey. The average daily milk yield, annual milk yield, and sales price buffalos milk of the enterprises were determined as 5.48±0.07 (kg), 1228.56±15.60 (kg/lactation), and USD1.06 (price/per kg), respectively. 3% of the produced raw milk was put on the market as raw milk, 20.9% as product, and 76.1% as raw milk + product. 81.54% of the processed milk was marketed as butter+cream+curd cheese, 7.69% as butter + cheese + curd cheese, and 10.77% is marketed as butter + cheese + yoghurt + curd cheese. It was determined that out of the companies selling raw milk, 88.7% sold to street milk + grocery stores and 11.3% sold to daily farms. As a result, in order to ensure sustainable buffalo breeding in Igdır province, buffalo milk collection centers, processing facilities, buffalo breeders' union should be established. Anatolian water buffaloes reared in Igdir city should be protected in order to protect the gene resources. Non-native buffalo insemination should not be allowed. Otherwise, it should be remembered that the heads rearing in each region are adapted into the region they inhabit in. Matings made to increase the amount of milk can affect negatively the properties like butter and cream yield. However, kinship degeneration should not be allowed in animals raised in the province. Mating of cows should be done with a system.